2021
DOI: 10.1111/opn.12380
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assessed foot health in older people with rheumatoid arthritis—A cross‐sectional study

Abstract: Background Foot and ankle problems are especially common in patients with RA, causing significant disability and limitation in daily activities. Previous studies have mainly focussed on foot problems in the adult population whilst the evidence of foot health in the older population is scarce. Objectives The aim of the study was to analyse self‐assessed foot health and associated factors in older people with rheumatoid arthritis (RA). Methods The study applied a descriptive cross‐sectional survey design and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Because elderly with RA live with complex foot problems, they need health services related to foot problems. There is also need to develop and implement care practices to relieve foot pain and support foot health and functional ability in elderly with RA [25]. Parallel to current studies, our study once again emphasized the negative effects of foot/ankle problems in individuals with RA and revealed that these problems increase with increasing age.…”
Section: Stolt Et Al (2017)supporting
confidence: 75%
“…Because elderly with RA live with complex foot problems, they need health services related to foot problems. There is also need to develop and implement care practices to relieve foot pain and support foot health and functional ability in elderly with RA [25]. Parallel to current studies, our study once again emphasized the negative effects of foot/ankle problems in individuals with RA and revealed that these problems increase with increasing age.…”
Section: Stolt Et Al (2017)supporting
confidence: 75%
“…Foot self-care is not possible for every patient because of physical restrictions or deficits in foot self-care knowledge [ 12 ]. Therefore, in the health care system, there should be equal access to podiatry services when foot self-care is decreased or impossible.…”
Section: Discussionmentioning
confidence: 99%
“…The most common foot problems are joint disorders, toenail problems such as thickened toenails and skin problems such as corns and calluses on the toes and soles of the feet [ 7 , 11 ]. Moreover, foot pain in PwRA is reported to be prevalent and in some studies even 70% of PwRA is reporting persistent foot pain [ 3 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Half of the respondents had visited a health care professional because of foot problems. Previous evidence suggests that people with rheumatic and musculoskeletal disease frequently consider their feet to be neglected in the context of broader medical consultations [ 34 , 35 ]. The findings of this study appear to substantiate this, with a high proportion of respondents seeking additional support outside of specialist centre consultations.…”
Section: Discussionmentioning
confidence: 99%